The removal of Perak's Menteri Besar from constitutional perspective / Kamal Hadi Ahmad Zaki, Muhammad Syafiq Aminudin, Mohd Radzi Mohd Sani - Ahmad Zaki, Kamal Hadi; Aminudin, Muhammad Syafiq; Mohd Sani, Mohd Radzi (2009)
The issue of the removal of Perak's Menteri Besar in constitutional perspective has brought lots of dilemma which has opened vast legal loopholes in the governance of constitution in our country. Therefore, this research aims are to explore the legal aspect in the State of Perak by examine the validity of the resignation letters made by the 3 Perak State Assemblymen, examine the powers vested in the Sultan of Perak's in dismissing the Menteri Besar and examine whether the procedural aspects of the removal of former Menteri Besar of Perak in accordance with the provision of the Perak's Constitution. The first chapter in this research provides the introduction of our draft proposal in conducting this research. The next chapter provides the power of Sultan and State Ruler on which this chapter discuss more on the discretionary powers of Sultan and State Ruler references with Federal Constitution and Perak Constitution. Further on chapter three it provides the cases study which relating with our research paper. Next, chapter four provides the current judgement in High Court and Court of Appeal in Perak's present crisis. Lastly, chapter five provides findings and conclusion. The issue of the removal of Perak Menteri Besar is still waiting to be heard at Federal Court, for that it is important for our group to analyze all the possible and relevant issue to achieve a precise outcome in this research.